Acute PD: Evidence, Guidelines, and Controversies☆ - Ponce, Daniela; Balbi, Andre; Cullis, Brett (Elsevier, 2017)
Peritoneal dialysis (PD) may be a feasible, safe, and complementary alternative to hemodialysis not only in the chronic setting, but also in the acute setting. It previously was widely accepted for acute kidney injury (AKI) treatment, but its practice decreased in favor of other types of extracorporeal therapies. The interest in PD to manage AKI patients has been reignited and PD now frequently is used in developing countries because of its lower cost and minimal infrastructural requirements. Studies from these countries have shown that, with careful thought and planning, critically ill patients can be treated successfully using PD. Some of the classic limitations of PD use in AKI, such as a high chance of infectious and mechanical complications and poor metabolic control, have been overcome with the use of cyclers, flexible catheters, and a high volume of dialysis fluid. However, in developing countries the infrastructure for quality research often is lacking and the result has been limited evidence on standardized treatment regimens such as indications, dosing, and technical failure and mortality. The recent publication of the International Society for Peritoneal Dialysis guidelines for PD in AKI have tried to address these issues and provide an evidence-based standard by which to initiate therapy. In this article, advances in technical aspects and the advantages and limitations of PD are discussed, and recent literature on clinical experience with PD for the treatment of AKI patients is reviewed.
Keywords: acute; acute kidney injury; critical care; Peritoneal dialysis; sepsis